Pengaruh return on equity dan debt to equity ratio terhadap stock return - Alpiner Tamba (Jurnal Riset Pendidikan Ekonomi, 2022)
This study aims to examine the effect of Return On Equity (ROE) and Debt to Equity Ratio (DER) on Stock Prices of Food and Beverages Sector Companies Listed on the Indonesia Stock Exchange. The data used in this research is secondary data which comes from the financial statements of companies on the Indonesia Stock Exchange. The population used in this study were all companies in the food and beverage sector listed on the IDX. This study uses purposive sampling technique with predetermined criteria. The number of samples used in this study were 7 companies. The analytical method used is multiple linear regression analysis.